ROMANTICISM: THE LITERATURE OF NATURALISM AND REALISM - Khudoyberdiyeva Gulasal Shukhratovna (International Scientific and Current Research Conferences, 2024)
The Romantic era, spanning the late 18th to the mid-19th century, is often characterized by its emphasis on emotion, individualism, and the sublime beauty of nature. However, a deeper exploration reveals that Romanticism also laid the groundwork for the subsequent literary movements of naturalism and realism. This article delves into how Romanticism, while distinct in its ideals and stylistic approaches, paved the way for the more grounded and empirically focused genres of naturalism and realism. By examining key works and authors, we aim to uncover the intrinsic connections and evolutionary trajectory from Romanticism to these later movements.